1979
DOI: 10.1016/0304-3940(79)95356-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive response in spontaneously hypertensive rats following microinjection of α-methylnoradrenaline in the caudal brain-stem

Abstract: SUMMARYLocal microinjection of 1.25 nmol (-)-a-methylnoradrenaline in the Arregion of the nucleus tractus solitarii (NTS) caused a decrease of blood pressure and heart rate in both spontaneous hypertensive rats (SHR) and Wistar-Kyoto (W/K) rats. Although the maximal responses in both strains did not differ, the decrease in blood pressure lasted longer in the SHR. These results do not support the concept of a diminished sensitivity of catecholaminergic receptors in the NTS of SHR to a-methylnoradrenaline.We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We found that the hypotensive effects of activating α 2 ‐adrenoceptors via an intra‐NTS guanfacine microinjection were attenuated in hypertensive SHRs (Figure A), whereas Zandberg and de Jong did not find a difference between SHRs and WKY rats using a microinjection of α‐methylnoradrenaline into the NTS (Zandberg and de Jong, ). This difference might reflect the activity of α‐methylnoradrenaline as an agonist at β‐adrenoceptors (De Jong and Nijkamp, ) and the higher affinity of guanfacine for α 2A ‐adrenoceptors (Uhlen and Wikberg, ; Kanagy, ).…”
Section: Discussionmentioning
confidence: 92%
“…We found that the hypotensive effects of activating α 2 ‐adrenoceptors via an intra‐NTS guanfacine microinjection were attenuated in hypertensive SHRs (Figure A), whereas Zandberg and de Jong did not find a difference between SHRs and WKY rats using a microinjection of α‐methylnoradrenaline into the NTS (Zandberg and de Jong, ). This difference might reflect the activity of α‐methylnoradrenaline as an agonist at β‐adrenoceptors (De Jong and Nijkamp, ) and the higher affinity of guanfacine for α 2A ‐adrenoceptors (Uhlen and Wikberg, ; Kanagy, ).…”
Section: Discussionmentioning
confidence: 92%